2017
DOI: 10.1002/jso.24866
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of common risk stratification indices to predict outcomes among stage IV cancer patients with bowel obstruction undergoing surgery

Abstract: ASA, CCI, and mFI are limited in their ability to predict postoperative adverse events among DMa patients undergoing surgery for bowel obstruction. These data suggest that a more tailored preoperative risk stratification tool would improve treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Most previous studies of prolonged hospitalization have focused on specific sub-groups of patients such as orthopaedic procedures [ 21 , 24 , 26 , 29 , 30 , 31 , 39 ], cardiovascular disease [ 13 , 15 , 17 , 36 , 37 , 38 ], solid organ transplantation [ 33 , 50 ], or oncological conditions [ 11 , 14 , 18 , 20 , 27 , 28 , 34 , 35 ] ( Supplementary Table S7 ). A limited number of studies have examined the epidemiology of prolonged hospitalization in internal medicine patients [ 23 , 45 , 51 ] but only one of these was multi-centre in nature [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies of prolonged hospitalization have focused on specific sub-groups of patients such as orthopaedic procedures [ 21 , 24 , 26 , 29 , 30 , 31 , 39 ], cardiovascular disease [ 13 , 15 , 17 , 36 , 37 , 38 ], solid organ transplantation [ 33 , 50 ], or oncological conditions [ 11 , 14 , 18 , 20 , 27 , 28 , 34 , 35 ] ( Supplementary Table S7 ). A limited number of studies have examined the epidemiology of prolonged hospitalization in internal medicine patients [ 23 , 45 , 51 ] but only one of these was multi-centre in nature [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this cutoff was chosen a priori. Other studies have variably defined prolonged hospitalization as admissions lasting more than seven days [ 19 , 23 , 29 , 37 , 38 ] or above the 75th centile for length of stay [ 11 , 12 , 14 , 15 , 17 , 20 , 26 , 27 , 30 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, frailty is frequently accompanied by the coexistence of multi-morbidity, being more frequent with increasing degrees of frailty [33]. However, while preoperative comorbidities and ASA classi cation are widely accepted as perioperative risk strati cation tools and associated with higher risks of complications and mortality [34], the predictive value of frailty assessment instruments in conjunction with co-morbidity or perioperative complications on mortality is still limited in literature [35].…”
Section: Impact Of Frailty On Postoperative Outcomes In Patients Recementioning
confidence: 99%
“…Our previous work analyzing a large statewide database indicated that compared to medical management, surgical management of malignant bowel obstructions was associated with increased complications, increased in-hospital mortality, and lower rates of discharges to home (2). This is made more difficult by the finding that common risk stratification tools (American Society of Anesthesiology classification, Charlson comorbidity index, and modified frailty score), do not adequately predict postoperative adverse events in this population (3). These considerations are especially challenging for patients receiving chemotherapy, as both invasive surgery and chemotherapy require fit patients with good performance status to optimize the risk/benefit ratio of multimodality therapy.…”
Section: Introductionmentioning
confidence: 99%